Impact of Capital Structure on the Performance of Nigerian Banks - Tunde, Matemilola Bolaji (2007)
Capital structure has attracted intense debate and scholarly attention in the financial management for over 40 years. However, the context of West Africa, capital structure has received little attention. This research attempts to fill this gap by analyzing and assessing the effect of debt and equity on the performance of 15 banks in Nigeria. The results indicate that debt has significant negative effect while equity has significant positive effect on the performance of Nigerian banks.